Revising the priorities during the pandemic in the light of Islamic legal maxims - Muhsin, Sayyed Mohamed (2022)
Fiqh al-muwāzanah (jurisprudence of comparison) enables the jurists to produce the finest potential scenarios from available options if they are mutually exclusive. The concept of muwāzanah is equally vital for individual, society, and nation to secure the best choice and to evade maximum evil during the process of decision making on various aspects including but not limited to social, economic, political, cultural, and educational. One of its major benefits is that it will make religion appear easier and more merciful. The primary prerequisite for muwāzanah is the capability for classification and arrangement of priorities conforming to the Sharīʿah standards. Likewise, thorough awareness of maqāṣid al- sharīʿah (higher objectives of sharīʿah) and competent knowledge about the field he/she deals with are required for eligibility to conduct muwāzanah. For example, knowledge about the legal mandates and ethical codes of the medical profession is needed for muwāzanah in healthcare issues. If otherwise, he/she must consult with experts and/or seek relevant legal advice. In addition, if muwāzanah is on any social issue, it should be with consultation (shūrā) and collective independent interpretation of the legal sources (ijtihād jamāʿī). Muwāzanah is comparison between (1) conflicting benefits, (2) conflicting evils or (3) evil that conflicts with benefit. This process helps to find which benefit is greater that needs to be preferred, which evil is greater that needs to be eliminated.